2012
DOI: 10.1016/j.amjsurg.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of emergency treatment of bleeding esophageal varices in cirrhosis for hepatocellular carcinoma

Abstract: Long-term screening by AFP and ultrasound plus selective CT failed to detect HCC at a curable stage. The detection of HCC in cirrhotic patients with BEV remains a serious, unsolved problem. The use of CT for routine screening warrants consideration despite increased costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Also, malignant tumor cells can activate invasion and metastasis during early tumorigenesis . Intrahepatic metastatic HCC at this stage may not be detectable using current detection methods . Therefore, distant intrahepatic recurrence may occur before treatment and could not be well controlled by the two ablation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Also, malignant tumor cells can activate invasion and metastasis during early tumorigenesis . Intrahepatic metastatic HCC at this stage may not be detectable using current detection methods . Therefore, distant intrahepatic recurrence may occur before treatment and could not be well controlled by the two ablation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the over-riding importance of emergency treatment of variceal bleeding, from 1958 to 2011 we conducted and reported studies of emergency therapy in patients with cirrhosis (Orloff, 1967;Orloff et al, 1980;Orloff et al, 1992); Orloff et al, 1994;Orloff et al, 1995a;Orloff et al, 2009a;Orloff et al, 2009b;Orloff et al, 2011a;Orloff et al, 2011b;Orloff et al, 2010;Orloff et al, 2011c;Orloff et al, 2011d;Orloff et al, 2011e;Orloff et al, 2011f;Orloff et al, 2011g;Orloff et al, 2011h;Orloff et al, 2011i). Our studies have been distinguished by three features that, together, make them different from other reported investigations.…”
Section: Introductionmentioning
confidence: 77%
“…The question is, can cirrhotic patients tolerate an operation of this magnitude when it is performed as an emergency in the face of bleeding? To answer this question, we have conducted prospective studies of emergency PCS (EPCS) over the past 47 years, as follows: (1) an unrandomized study of 400 unselected patients who underwent EPCS; (2) a RCT of EPCS versus emergency medical therapy involving 43 patients at our Veterans Administration Hospital; (3) an unrandomized study of 94 unselected, consecutive patients with Child's class C cirrhosis; (4) a RCT of portacaval shunt versus endoscopic sclerotherapy in 518 unselected patients bleeding from gastric varices; (5) a n u n r a n d o m i z e d s t u d y i n 1 2 p a t i e n t s w i t h u n c o n t r o l l a b l e b l e e d i n g f r o m p o r t a l hypertensive gastropathy; (6) a NIH grant supported RCT of EPCS versus emergency endoscopic sclerotherapy (EST) that enrolled 211 patients who have had more than 10 years of follow-up or until death; and (7) a NIH grant supported RCT of TIPS versus EPCS that enrolled 154 patients who have been followed up for 5-10 years (Orloff, 1967;Orloff et al, 1980;Orloff et al, 1992;Orloff et al, 1994;Orloff et al, 1995a;Orloff et al, 2009a;Orloff et al, 2009b;Orloff et al, 2011a;Orloff et al, 2011b;Orloff et al, 2010;Orloff et al, 2011c;Orloff et al, 2011d;Orloff et al, 2011e;Orloff et al, 2011f;Orloff et al, 2011g;Orloff et al, 2011h;Orloff et al, 2011i;Orloff & Bell, 1983;Bell, et al, 1981;Orloff, 1968;Orloff, 1969;Orloff et al, 1974;Orloff et al, 1975;Orloff & Bell, 1986;Orloff et al, 1995b;Orloff et al, 1997) . The unique features of our studies that, together, make them different from other reported investigations are as follows: (1) EPCS was undertaken within 24 h of initial contact of the patient with our institution in one study and within 8 h in the other six studies; (2) the patients were unselected, which means that all patients with bleeding varices, regardless of their condition ("all comers"), were entered in the studies and treated; (3) the studies were prospective, which means that the p...…”
Section: Emergency Portacaval Shunt For Bleeding Esophageal Varicesmentioning
confidence: 99%
“…Our recent publications provided detailed data on the clinical characteristics of the 211 patients including diagnostic findings, data on survival, data on control of bleeding, and data on PSE. 37…”
Section: Resultsmentioning
confidence: 99%
“…In several recent publications, we described the study in detail and reported the outcomes with regard to control of bleeding, survival, development of portal-systemic encephalopathy (PSE), costs of care, results of rescue portacaval shunt (PCS) for failed EST, and detection and treatment of hepatocellular carcinoma. 37 This report focuses on objective measures of long-term disability after discharge from the index hospital admission.…”
mentioning
confidence: 99%